On the Symmetric Central Configurations for the Planar 1 + 4-Body Problem - Chunhua Deng; Fengying Li; Shiqing Zhang (Complexity)
We study the planar symmetric central configurations of the 1 + 4-body problem where the symmetry axis does not contain any infinitesimal masses. Under certain assumptions, we find analytically some central configurations for suitable positive masses and also get some numerical results of symmetric central configurations where infinitesimal masses are not necessarily equal.